2016
DOI: 10.1097/icl.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of Thermal Pulsation (LipiFlow) in Meibomian Gland Dysfunction With Preteatment Meibography

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 38 publications
6
57
0
3
Order By: Relevance
“…Many studies [9][10][11][12][13][14][15][16][17][18][19] have reported that a single LipiFlow® treatment had a statistically significant greater reduction in dry eye symptoms than warm compresses at 1 month until 1 year post-treatment. In contrast to those findings, the results of the present study were the same as those of other reports 16,25 that did not demonstrate a statistically significant difference in the dry eye symptoms between the single LipiFlow® treatment and the twice-daily warm compresses, nor in the number of EMGs and LLTs, despite a tendency to improve those three parameters in the patients receiving the LipiFlow® treatment. The current study could not demonstrate a statistical difference in the dry eye symptoms of both treatments, and the mean SPEED scores found in this study were less than those reported by other researches.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies [9][10][11][12][13][14][15][16][17][18][19] have reported that a single LipiFlow® treatment had a statistically significant greater reduction in dry eye symptoms than warm compresses at 1 month until 1 year post-treatment. In contrast to those findings, the results of the present study were the same as those of other reports 16,25 that did not demonstrate a statistically significant difference in the dry eye symptoms between the single LipiFlow® treatment and the twice-daily warm compresses, nor in the number of EMGs and LLTs, despite a tendency to improve those three parameters in the patients receiving the LipiFlow® treatment. The current study could not demonstrate a statistical difference in the dry eye symptoms of both treatments, and the mean SPEED scores found in this study were less than those reported by other researches.…”
Section: Discussionsupporting
confidence: 86%
“…9,10 The SingHealth Centralized Institutional Review Board has approved this study, and the Tenets of the Declaration of Helsinki were followed. From February 2012 to March 2013, all patients who met the eligibility criteria at the dry eye clinic in Singapore National Eye Center went through study briefing and were invited for screening.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…9 The clinical efficacy of Lipiflow, a form of thermopulsation treatment compared with warm towel, was also examined. 10 However, none of these reports have included the effect of lid warming on TE rates. The aim of the current report is to establish the longitudinal effects of eyelid warming on TE rates with eyelid warming treatment over 12 weeks of treatment period.…”
mentioning
confidence: 99%
“…[113,115] A clinical trial revealed that LipiFlow was able to improve symptoms of ocular irritation, and subsequently in 2011, the FDA approved LipiFlow as a medical device. [116,117] Although the treatment is an effective therapy for some patients, it is still not widely available due to its high cost. [117] Hence, additional numerous topical cost-effective pharmaceutical agents are being screened as a potential therapy for DED.…”
Section: Ocular Diseasesmentioning
confidence: 99%